2023
DOI: 10.12688/f1000research.129050.1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism studies and candidate genes associated with litter size traits in Indonesian goats. a systematic review

Abstract: Background: Litter size (LS) is a significant, challenging, and economical aspect of the goat industry in Indonesia. It is influenced by several different factors and genes; consequently, identifying potential genes and loci associated with litter size has become a genetic problem. Several genetic indicators have been found to be associated with litter size in goats. This has prompted the need to discuss candidate genes associated with litter size in goats in Indonesia. Methods: A systematic review was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Given the importance of the KiSS1 gene as a regulator of puberty onset, the current study supports the hypothesis that KiSS1 gene polymorphisms have some relationship with fertility in small ruminants. The significant correlation between the TT genotype and larger litter size in the Kacang and Boerka breeds (P<0.05) is in line with earlier findings by An et al (2013), El-Tarabany et al (2017), and Abuzahra et al (2023. Furthermore, Cao et al (2010) also discovered a link between allele C of the 296 loci and allele deletion of the 1960-1977 locus in the caprine KiSS1 gene and large litter size in the Jining Grey breed.…”
Section: Association Of the Kiss1 Gene (G1909t>c) With Litter Sizesupporting
confidence: 87%
See 1 more Smart Citation
“…Given the importance of the KiSS1 gene as a regulator of puberty onset, the current study supports the hypothesis that KiSS1 gene polymorphisms have some relationship with fertility in small ruminants. The significant correlation between the TT genotype and larger litter size in the Kacang and Boerka breeds (P<0.05) is in line with earlier findings by An et al (2013), El-Tarabany et al (2017), and Abuzahra et al (2023. Furthermore, Cao et al (2010) also discovered a link between allele C of the 296 loci and allele deletion of the 1960-1977 locus in the caprine KiSS1 gene and large litter size in the Jining Grey breed.…”
Section: Association Of the Kiss1 Gene (G1909t>c) With Litter Sizesupporting
confidence: 87%
“…Various studies have been carried out by associating the KISS1 gene with litter size; the research of Abuzahra et al (2023) showed that the KISS1 gene is a candidate gene that affects litter size. An et al (2013) and El-Tarabany et al (2017) discovered a polymorphism in the number of KISS1 gene loci correlating with litter size.…”
Section: Introductionmentioning
confidence: 99%
“…In Türkiye, as in the world, fecundity gene research has been focused more on native sheep breeds (Karslı et al, 2012;Çelikeloğlu et al, 2022;Gedik 2021;Kırıkçı, 2023a;Kırıkçı, 2023b), while there are significant shortcomings in the research on goat fecundity genes. Recently, there has been an increasing interest in fecundity genes in goats (Maitra et al, 2023;Song et al, 2023;Abuzahra et al, 2023). A study by Maitra et al (2023) to understand the genetic mechanism of prolificacy in goats found that the genes BMPR1B, BMP15 and GDF9 are highly expressed in goat ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep's "litter size" is one of their most valuable economic characteristics (Schmidová et al 2014;Al-Thuwaini et al 2020;Farrell et al 2022;Abuzahra et al 2023), which means the average number of lambs born to a single ewe during lambing season (Ziadi et al 2021;Tao et al 2021) Prolificity, also known as litter size, is the indication of sheep's reproductive efficiency that has been subjected to the most research. Prolificity is defined as the average number of lambs born from each pregnancy (Ahlawat et al 2016;Ayele and Urge 2019;Hernández et al 2019;Medina-Montes et al 2021).…”
Section: Introductionmentioning
confidence: 99%